Mapping of the determinants that cause Burnout in health professionals in the context of Covid-19: scoping review (Research, Society and Development, 2022)
Objective: This study aimed to map the determinants that cause Burnout in health professionals in the face of the Covid-19 pandemic. Methodology: This is a scope review, with a search for articles from the database: PubMed via MEDLINE, CINAHL via EBSCOhost, SciVerse (SCOPUS), LILACS and gray literature, through the controlled vocabulary of Medical Subject Headings (MESH), by the following descriptors: Health Personnel; Covid-19; Professional burnout. Results: The 54 selected articles on the subject are national and international. Regarding the types of studies, there is a prevalence of observational studies, most of the cross-sectional type. Among the main determinants, we can observe: Excessive workload; Lack of Personal Protective Equipment; Difficulty in accessing a test for Covid-19; Long working hours; Fear of contamination by Covid-19; Fear of contaminating family members; Acting on the front line in the fight against Covid-19. Conclusion: In view of the results found, it is expected that this information can help health managers in the best interventions to mitigate the factors that cause Burnout in health professionals. In addition, to assist in future research on the topic addressed